2016
DOI: 10.1080/23279095.2016.1214835
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of the HIV dementia scale and the international HIV dementia scale in screening for HIV-associated neurocognitive disorders among Spanish-speaking adults

Abstract: Given that neurocognitive impairment is a frequent complication of HIV-1 infection in Spanish-speaking adults, the limited number of studies assessing HIV-associated neurocognitive disorders (HAND) in this population raises serious clinical concern. In addition to being appropriately translated, instruments need to be modified, normed, and validated accordingly. The purpose of the current study was to examine the diagnostic utility of the HIV Dementia Scale (HDS) and International HIV Dementia Scale (IHDS) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(57 reference statements)
0
8
0
3
Order By: Relevance
“…Despite the well-established IHDS screening methods routinely used for American and African populations, recent evaluations of the clinical utility of the IHDS, compared with the HIV Dementia Scale (HDS), reveal divergent outcomes. In one study among Spanish-speaking adults, the HDS showed more appropriate screening results and clinical utility in terms of time and cost compared with the IHDS[15]. Conversely,a separate study among German-speaking people recommended the IHDS as a useful screening tool [16], suggesting that the pattern of HAD symptoms and their severity could be linked to the genetic background and lifestyle of individual patients.…”
Section: Hiv-associated Neuropathological Complicationsmentioning
confidence: 99%
“…Despite the well-established IHDS screening methods routinely used for American and African populations, recent evaluations of the clinical utility of the IHDS, compared with the HIV Dementia Scale (HDS), reveal divergent outcomes. In one study among Spanish-speaking adults, the HDS showed more appropriate screening results and clinical utility in terms of time and cost compared with the IHDS[15]. Conversely,a separate study among German-speaking people recommended the IHDS as a useful screening tool [16], suggesting that the pattern of HAD symptoms and their severity could be linked to the genetic background and lifestyle of individual patients.…”
Section: Hiv-associated Neuropathological Complicationsmentioning
confidence: 99%
“…From a total of 54 unique studies identified using the search strategy and assessed in full-text, we included in our systematic review and meta-analysis 15 studies [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The characteristics of the studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Patient Selection domain, the risk of bias was reduced by selecting only cross-sectional studies. A random or consecutive sample of patients was reported in eight studies [ 53 , 56 , 57 , 59 , 60 , 63 , 64 , 66 ]. One study enrolled the patients based on CD4 count (<350 cells/mm 3 ) [ 61 ]; one study included only PLWH with moderate to severe HAND [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…States have shown that instruments such as the HIV Dementia Scale may be appropriate for NP screening in this population, while other instruments such as the International HIV Dementia Scale may not perform as well (Levine et al, 2011;López et al, 2016;Mindt et al, 2003). Instruments such as HIV/University of Miami Annotated Neuropsychological test battery in Spanish (HUMANS) have been developed for use in Spanish and English speakers, but these need validations in large comparative studies of Spanish versus English speakers (Wilkie et al, 2004).…”
Section: Small Studies Limited To Spanish Speakers With Hiv In the Unmentioning
confidence: 99%